Le rôle des sociétés de sécurité privées dans la sécurisation du détroit de Malacca (2000-2008) - Gilles Bonavita (EchoGéo)
The Strait of Malacca well known all over the world as active area of pirates, found since 2005 a peace in this domain. If it is certain that the strong political willings of the waterside States came to buid a stake in joint work of the national means with the support of major powerful countries, we cannot push aside the discreet and certainly effective work led by private armed maritime security companies; Unpopular, very criticized these companies are only bringing an answer to a strong demand.